Heavy calcium carbonate with low oil absorption value as well as preparation method and application thereof
Through the second-stage modification process of heavy calcium carbonate, the oil absorption value is reduced, and the problem of poor compatibility in soft PVC is solved, the tensile strength and hue stability are improved, the use of plasticizer is reduced, and the amount of plasticizer is reduced. Production costs and extend service life.
Patent Information
- Application Number
- CN202411441725.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-17
AI Technical Summary
The existing heavy calcium carbonate has problems such as poor tensile strength, unstable hue and poor compatibility in soft PVC, which leads to the migration and precipitation of plasticizers, affecting production costs and usage performance.
The second-stage modification process is used to dry, dehumidify, infiltrate and surface coat modification of the calcite powder. The epoxy plasticizer and ester lubricant are used to reduce the oil absorption value, and the particles are grinded through ball milling equipment. More regular and improve the modification effect.
It significantly reduces the oil absorption value of heavy calcium carbonate, improves compatibility and tensile strength with PVC, reduces the use of plasticizer, reduces the production cost, and extends the service life of the product.
Smart Images

Figure BDA0005086514130000101 
Figure BDA0005086514130000111 
Figure BDA0005086514130000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional inorganic non-metallic materials, and in particular to a heavy calcium carbonate with low oil absorption value, and a preparation method and application thereof. Background Art
[0002] Soft PVC (polyvinyl chloride plastic), also known as plasticized polyvinyl chloride plastic, refers to polyvinyl chloride plastic with added plasticizers. Soft PVC is widely used in plastic products such as packaging materials, wires and cables, artificial leather, films and sealing materials.
[0003] Heavy calcium carbonate is an inorganic powder prepared by physical grinding of natural calcium carbonate salt minerals such as calcite, marble, and dolomite. As an inorganic powder filler, it is often used as a filler for soft PVC because of its high chemical purity, high inertness, good thermal stability, non-toxicity, tastelessness, and odorlessness. At the same time, its low price further expands its application in soft PVC.
[0004] Oil absorption value refers to the ability of powder materials to absorb oil and fat, and is one of the important indicators to measure the oil absorption performance of powder materials. The oil absorption value is usually expressed as the amount of oil required for 100g of powder material. The oil absorption value directly affects the use effect of the material. The higher the oil absorption value of heavy calcium carbonate, the more plasticizer is needed for soft PVC, and the production cost is high; at the same time, it is easy to cause poor compatibility between heavy calcium carbonate and PVC resin, and defects will occur during processing and use.
[0005] Since soft PVC needs to add a lot of plasticizers for processing, the plasticizers are easy to migrate and precipitate during processing and subsequent use, affecting its performance. In order to reduce the amount of plasticizers used in soft PVC, heavy calcium carbonate with low oil absorption value should be used in it. The lower the oil absorption value of calcium carbonate, not only can the production cost be reduced, but also because of its low oil absorption value, it is easier to disperse in the PVC substrate, increasing its compatibility.
[0006] The traditional method of reducing the oil absorption value of heavy calcium carbonate is to use a physical coating surface modification process to coat the surface of heavy calcium carbonate with surface modifiers such as stearic acid and coupling agent for activation treatment. This process can reduce the oil absorption value of heavy calcium carbonate, but due to the special processing and use requirements of soft PVC, calcium carbonate with stearic acid and coupling agent can easily cause the migration and precipitation of plasticizers, affecting its printing performance and accelerating its aging performance. For example, in PVC calendered film, the use of calcium carbonate containing stearic acid affects the ink absorption performance; in PVC hoses, the use of calcium carbonate containing stearic acid affects its color stability; in PVC laminating film, the use of calcium carbonate containing stearic acid can easily cause problems such as lamination and loose bonding.
[0007] Based on this, there is an urgent need for a heavy calcium carbonate with low oil absorption value specifically used in soft PVC. Summary of the invention
[0008] The purpose of the present invention is to provide a heavy calcium carbonate with low oil absorption value and a preparation method and application thereof, so as to solve the technical problems in the prior art that heavy calcium carbonate has poor tensile strength, unstable hue, poor compatibility with PVC and weak bonding in soft PVC.
[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0010] The present invention provides a method for preparing heavy calcium carbonate with low oil absorption value, comprising the following steps:
[0011] The calcite powder is sequentially subjected to drying and dehumidification, infiltration modification and surface coating modification to obtain heavy calcium carbonate with low oil absorption value;
[0012] The modifying agent used in the impregnation modification is an epoxy plasticizer;
[0013] The modifying agent used in the surface coating modification is an ester lubricant.
[0014] Furthermore, the calcite powder meets the following conditions: D50 is 2-3 μm, D97 is 5.5-8 μm, and the oil absorption value is 25-35 mL / 100 g.
[0015] Furthermore, the drying and dehumidification temperature is 105-120° C., the drying and dehumidification time is 10-50 min, and the drying and dehumidification is carried out under stirring, and the stirring speed is 30-90 r / min.
[0016] Furthermore, the epoxy plasticizer includes one or more of epoxidized soybean oil, epoxidized linseed oil, epoxidized butyl oleate, epoxidized octyl oleate and epoxidized dioctyl tetrahydrophthalate.
[0017] Furthermore, the temperature of the impregnation modification is 50-80° C., the time of the impregnation modification is 15-60 min, and the impregnation modification is carried out under stirring at a stirring speed of 50-150 r / min.
[0018] Furthermore, the ester lubricant includes one or more of glyceryl monostearate, stearyl stearate, distearyl phthalate and pentaerythritol adipic acid-stearate.
[0019] Furthermore, the mass of the epoxy plasticizer is 0.4 to 0.9 of the mass of the calcite powder;
[0020] The mass of the ester lubricant is 3-9‰ of the calcite powder.
[0021] Furthermore, the surface coating modification temperature is 70-100° C., the surface coating modification time is 10-40 min, and the surface coating modification is carried out under stirring at a stirring speed of 250-500 r / min.
[0022] The present invention provides a heavy calcium carbonate with low oil absorption value prepared by the preparation method, characterized in that the heavy calcium carbonate with low oil absorption value meets the following conditions: D50 is 2 to 3 μm, D97 is 5 to 7 μm, and the oil absorption value is 15 to 18 mL / 100 g.
[0023] The present invention also provides an application of the heavy calcium carbonate with low oil absorption value as an auxiliary agent in soft PVC.
[0024] Beneficial effects of the present invention:
[0025] (1) In the present invention, heavy calcium carbonate is modified. Since the acid and alcohol of the synthetic ester can be selected in a diversified manner and have different functional groups and side chains, different modification additives can be selected according to the application scenarios of soft PVC, thereby expanding the application scope of heavy calcium carbonate in soft PVC.
[0026] (2) The present invention adopts a two-stage surface modification process, and the modification temperature setting can be selected according to the selection of the auxiliary agent in each stage. Compared with the traditional single high-speed mixing and stirring for surface modification, the first stage of the present invention adopts low-speed kneading and the second stage adopts high-speed mixing. Compared with the traditional processing technology, the energy consumption of the present invention is lower.
[0027] (3) The calcium carbonate raw powder selected in the present invention is ultrafine calcium carbonate ground by ball milling equipment, because the calcium carbonate particles processed by ball milling equipment have more regular and uniform morphology, narrower particle distribution, better fineness uniformity, and its oil absorption value will be lower after surface modification.
[0028] (4) The two-stage modification process adopted in the present invention plays a role of wetting and dispersing in the first stage of the modification process, which reduces the polarity of the surface of calcium carbonate and makes the surface of heavy calcium carbonate have both polar groups and non-polar groups. This makes it easier to match the ester modification additive in the second stage of the modification process, and it is easier to form a strong bonding effect on the surface of the infiltrated calcium carbonate, thereby fully realizing the improvement of the modification effect and reducing the oil absorption value. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing heavy calcium carbonate with low oil absorption value, comprising the following steps:
[0030] The calcite powder is sequentially subjected to drying and dehumidification, infiltration modification and surface coating modification to obtain heavy calcium carbonate with low oil absorption value;
[0031] The modifying agent used in the impregnation modification is an epoxy plasticizer;
[0032] The modifying agent used in the surface coating modification is an ester lubricant.
[0033] In the present invention, the calcite powder satisfies the following conditions: D50 is 2 to 3 μm, preferably 2.1 to 2.8 μm, and more preferably 2.2 to 2.6 μm; D97 is 5.5 to 8 μm, preferably 6 to 7.5 μm, and more preferably 6.5 to 7 μm; the oil absorption value is 25 to 35 mL / 100 g, preferably 27 to 33 mL / 100 g, and more preferably 28 to 31 mL / 100 g.
[0034] In the present invention, the calcite powder is processed by a ball mill to make the surface morphology of the heavy calcium carbonate particles closer to a spherical shape. During the modification process, it is easier to wrap the modification aid on the surface of the particles, thereby achieving a better effect of reducing the oil absorption value.
[0035] In the present invention, the temperature of the drying and dehumidification is 105-120°C, preferably 108-118°C, and more preferably 110-115°C; the time of the drying and dehumidification is 10-50 min, preferably 15-45 min, and more preferably 20-40 min; the drying and dehumidification is carried out under stirring, and the stirring speed is 30-90 r / min, preferably 35-85 r / min, and more preferably 40-80 r / min.
[0036] In the present invention, the epoxy plasticizer includes one or more of epoxidized soybean oil, epoxidized linseed oil, epoxidized butyl oleate, epoxidized octyl oleate and epoxidized dioctyl tetrahydrophthalate, preferably one or more of epoxidized soybean oil, epoxidized linseed oil, epoxidized octyl oleate and epoxidized dioctyl tetrahydrophthalate, and further preferably one or more of epoxidized soybean oil, epoxidized linseed oil and epoxidized dioctyl tetrahydrophthalate.
[0037] In the present invention, the mass of the epoxy plasticizer is 0.4 to 0.9 of the mass of the calcite powder, preferably 0.5 to 0.8, and more preferably 0.6 to 0.7.
[0038] In the present invention, the modifier added by impregnation modification is an epoxy plasticizer, which has the dual functions of plasticization and stabilization in the processing of soft PVC. The epoxy plasticizer can absorb the hydrogen chloride released by the polyvinyl chloride molecules due to thermal and light degradation, stabilize the active chlorine atoms on the polyvinyl chloride chain, prevent continuous catalytic decomposition, and extend the service life of the product. They have good anti-extraction and anti-migration properties, can effectively reduce the migration of heavy calcium carbonate in soft PVC, and at the same time wet and disperse the heavy calcium carbonate, which plays an auxiliary effect of reducing the oil absorption value.
[0039] In the present invention, the temperature of the infiltration modification is 50-80°C, preferably 55-75°C, and more preferably 60-70°C; the time of the infiltration modification is 15-60min, preferably 20-55min, and more preferably 25-50min; the infiltration modification is carried out under stirring, and the stirring speed is 50-150r / min, preferably 55-145r / min, and more preferably 60-140r / min.
[0040] In the present invention, the ester lubricant includes one or more of glyceryl monostearate, stearyl stearate, distearyl phthalate and pentaerythritol adipic acid stearate, preferably one or more of stearyl stearate, distearyl phthalate and pentaerythritol adipic acid stearate, and more preferably stearyl stearate and / or distearyl phthalate.
[0041] In the present invention, the mass of the ester lubricant is 3-9‰ of the calcite powder, preferably 3.5-8.5‰, and more preferably 4-8‰.
[0042] In the present invention, the modifier added for surface coating modification is an ester lubricant, which is a compound obtained by the reaction of alcohol and acid, also known as a carboxylic acid ester lubricant. Due to the uniqueness of its structure, ester lubricants have good compatibility with PVC and a small amount of addition. In this type of lubricant, the ester group and the unesterified hydroxyl group in the structure are polar groups, while the long carbon chains of fatty acids and fatty alcohols constitute the non-polar part. The ester group and hydroxyl group in the polar part have a strong affinity with PVC, playing the role of compatibility and internal lubrication; while the fatty acids and fatty alcohols in the non-polar part can play the role of external lubrication. The use of this type of additive to modify heavy calcium carbonate can not only have a significant effect on reducing the oil absorption value of calcium carbonate, but also have good processing fluidity and improve the plasticizing effect when used in soft PVC. Ester lubricants also have good heat resistance, generally with a heat resistance range of 200°C-320°C, which can meet the processing temperature requirements of soft PVC.
[0043] In the present invention, the temperature of the surface coating modification is 70-100°C, preferably 75-95°C, and more preferably 80-90°C; the time of the surface coating modification is 10-40min, preferably 15-35min, and more preferably 20-30min; the surface coating modification is carried out under stirring, and the stirring speed is 250-500r / min, preferably 280-450r / min, and more preferably 300-400r / min.
[0044] In the present invention, cooling is preferably performed after the surface coating modification treatment, and packaging is performed after cooling to room temperature to obtain heavy calcium carbonate with low oil absorption value.
[0045] The present invention provides a heavy calcium carbonate with low oil absorption value prepared by the preparation method, wherein the heavy calcium carbonate with low oil absorption value meets the following conditions: D50 is 2-3 μm, preferably 2.1-2.7 μm, and more preferably 2.2-2.6 μm; D97 is 5-7 μm, preferably 5.1-6.9 μm, and more preferably 5.2-6.8 μm; and the oil absorption value is 15-18 mL / 100 g, preferably 15-17 mL / 100 g, and more preferably 16 mL / 100 g.
[0046] The present invention also provides an application of the heavy calcium carbonate with low oil absorption value as an auxiliary agent in soft PVC.
[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] 400 kg of calcite powder with a fineness of D50 of 2.6 μm, D97 of 7 μm and an oil absorption value of 28 mL / 100 g was dried and dehumidified at 105° C., the impregnation modification time was 30 min, the drying and dehumidification were carried out under stirring, and the stirring speed was 60 r / min; after drying and dehumidification, 600,000 epoxidized soybean oil was added and impregnation modification was carried out at 60° C. for 30 min, the impregnation modification was carried out under stirring, and the stirring speed was 105 r / min; after impregnation modification, 5‰ stearyl stearate was added and surface coating modification was carried out at 90° C., the surface coating modification time was 30 min, the surface coating modification was carried out under stirring, and the stirring speed was 300 r / min; finally, the surface-coated calcium carbonate was cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0050] Example 2
[0051] 400 kg of calcite powder with a fineness of D50 of 2.6 μm, D97 of 7 μm and an oil absorption value of 28 mL / 100 g was dried and dehumidified at 110° C., the impregnation modification time was 30 min, the drying and dehumidification were carried out under stirring, and the stirring speed was 60 r / min; after drying and dehumidification, 3 / 10,000 epoxidized soybean oil and 3 / 10,000 epoxidized linseed oil were added to carry out impregnation modification at 65° C. for 30 min, the impregnation modification was carried out under stirring, and the stirring speed was 105 r / min; after impregnation modification, 6‰ stearyl stearate was added to carry out surface coating modification at 90° C., the surface coating modification time was 20 min, the surface coating modification was carried out under stirring, and the stirring speed was 350 r / min; finally, the surface-coated calcium carbonate was cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0052] Example 3
[0053] 400 kg of calcite powder with a fineness of D50 of 2.6 μm, D97 of 7 μm and an oil absorption value of 28 mL / 100 g was dried and dehumidified at 110° C., the impregnation modification time was 30 min, the drying and dehumidification were carried out under stirring, and the stirring speed was 60 r / min; after drying and dehumidification, 3 / 10,000 epoxidized soybean oil and 3 / 10,000 epoxidized linseed oil were added for impregnation modification at 65° C. for 30 min, the impregnation modification was carried out under stirring, and the stirring speed was 105 r / min; after impregnation modification, 3‰ stearyl stearate and 3‰ distearyl phthalate were added for surface coating modification at 90° C., the surface coating modification time was 20 min, the surface coating modification was carried out under stirring, and the stirring speed was 350 r / min; finally, the surface-coated calcium carbonate was cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0054] Example 4
[0055] 400 kg of calcite powder with a fineness of D50 of 2.6 μm, D97 of 7 μm and an oil absorption value of 28 mL / 100 g was dried and dehumidified at 110°C for 30 min under stirring at a speed of 60 r / min. After drying and dehumidification, 30,000 ppm of epoxidized soybean oil and 30,000 ppm of epoxidized linseed oil were added and the mixture was infiltrated and modified at 65°C for 30 min under stirring. The stirring speed is 105r / min; after the infiltration modification, 2‰ stearyl stearate, 2‰ distearyl phthalate and 2‰ pentaerythritol adipic acid-stearate are added for surface coating modification at 90°C, and the surface coating modification time is 20min. The surface coating modification is carried out under stirring, and the stirring speed is 350r / min; finally, the surface-coated calcium carbonate is cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0056] Example 5
[0057] 400 kg of calcite powder with a fineness of D50 of 2.1 μm, D97 of 5.5 μm and an oil absorption value of 31 mL / 100 g was dried and dehumidified at 110° C., the impregnation modification time was 30 min, the drying and dehumidification were carried out under stirring, and the stirring speed was 60 r / min; after drying and dehumidification, 3 / 10,000 epoxidized soybean oil and 3 / 10,000 epoxidized linseed oil were added to carry out impregnation modification at 65° C. for 30 min, the impregnation modification was carried out under stirring, and the stirring speed was 105 r / min; after impregnation modification, 3‰ stearyl stearate and 3‰ distearyl phthalate were added to carry out surface coating modification at 90° C., the surface coating modification time was 20 min, the surface coating modification was carried out under stirring, and the stirring speed was 350 r / min; finally, the surface-coated calcium carbonate was cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0058] Example 6
[0059] 400 kg of calcite powder with a fineness of D50 of 2.1 μm, D97 of 5.5 μm and an oil absorption value of 31 mL / 100 g was dried and dehumidified at 110°C for 30 min. The drying and dehumidification was carried out under stirring at a stirring speed of 60 r / min. After drying and dehumidification, 20,000 ppm of epoxidized soybean oil, 20,000 ppm of epoxidized linseed oil and 20,000 ppm of epoxidized dioctyl tetrahydrophthalate were added and the mixture was wetted and modified at 65°C for 30 min. The infiltration modification is carried out under stirring, and the stirring speed is 105r / min; after the infiltration modification, 2‰ stearyl stearate, 2‰ glyceryl monostearate and 2‰ distearyl phthalate are added for surface coating modification at 90°C, and the surface coating modification time is 20min. The surface coating modification is carried out under stirring, and the stirring speed is 350r / min; finally, the surface-coated calcium carbonate is cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0060] Example 7
[0061] 400 kg of calcite powder with a fineness of D50 of 2.1 μm, D97 of 5.5 μm and an oil absorption value of 31 mL / 100 g was dried and dehumidified at 110 ° C. The impregnation modification time was 30 min. The drying and dehumidification was carried out under stirring at a stirring speed of 60 r / min. After drying and dehumidification, 20,000 ppm of epoxy soybean oil, 20,000 ppm of epoxy oleic acid butyl ester and 20,000 ppm of epoxy oleic acid octyl ester were added and impregnated at 65 ° C for 3 0min, the infiltration modification is carried out under stirring, and the stirring speed is 105r / min; after the infiltration modification, 3‰ stearyl stearate and 3‰ glyceryl monostearate are added at 90°C for surface coating modification, and the surface coating modification time is 20min. The surface coating modification is carried out under stirring, and the stirring speed is 350r / min; finally, the surface-coated calcium carbonate is cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0062] Example 8
[0063] 400 kg of calcite powder with a fineness of D50 of 2.1 μm, D97 of 5.5 μm and an oil absorption value of 31 mL / 100 g was dried and dehumidified at 110° C., the impregnation modification time was 30 min, the drying and dehumidification were carried out under stirring, and the stirring speed was 60 r / min; after drying and dehumidification, 3 / 10,000 epoxy soybean oil and 3 / 10,000 epoxy oleic acid octyl ester were added to carry out impregnation modification at 65° C. for 30 min, the impregnation modification was carried out under stirring, and the stirring speed was 105 r / min; after impregnation modification, 3‰ stearyl stearate and 3‰ adipic acid-stearate pentaerythritol ester were added to carry out surface coating modification at 90° C., the surface coating modification time was 20 min, the surface coating modification was carried out under stirring, and the stirring speed was 350 r / min; finally, the surface-coated calcium carbonate was cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0064] Example 9
[0065] 400 kg of calcite powder with a fineness of D50 of 2.1 μm, D97 of 5.5 μm and an oil absorption value of 31 mL / 100 g was dried and dehumidified at 110°C for 30 min under stirring at a speed of 60 r / min. After drying and dehumidification, 30,000 ppm of epoxidized soybean oil and 30,000 ppm of epoxidized linseed oil were added and the mixture was infiltrated and modified at 65°C for 30 min under stirring. The surface is coated and modified at 90°C under stirring at a speed of 350 r / min. After the surface is coated and modified, 3‰ distearyl phthalate and 3‰ pentaerythritol adipic acid-stearate are added at a speed of 350 r / min. Finally, the surface-coated calcium carbonate is cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0066] Comparative Example 1
[0067] The heavy calcium carbonate with low oil absorption value is the ultrafine heavy calcium carbonate GY-616 produced by Qingyang Guangyuan New Materials Co., Ltd.
[0068] Comparative Example 2
[0069] The heavy calcium carbonate with low oil absorption value is the ultrafine heavy calcium carbonate GY-716 produced by Qingyang Guangyuan New Materials Co., Ltd.
[0070] Comparative Example 3
[0071] 400 kg of calcite powder with a fineness of D50 of 2.6 μm, D97 of 7 μm and an oil absorption value of 28 mL / 100 g is dried and dehumidified at 110° C. The impregnation modification time is 30 min, and the drying and dehumidification is carried out under stirring at a speed of 60 r / min. After drying and dehumidification, 3 / 10,000 epoxidized soybean oil and 3 / 10,000 epoxidized linseed oil are added and impregnated and modified at 65° C. for 30 min, and the impregnation modification is carried out under stirring at a speed of 105 r / min. After impregnation and modification, the powder is cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0072] Comparative Example 4
[0073] 400 kg of calcite powder with a fineness of D50 of 2.6 μm, D97 of 7 μm and an oil absorption value of 28 mL / 100 g was dried and dehumidified at 110°C, the infiltration modification time was 30 min, the drying and dehumidification were carried out under stirring, and the stirring speed was 60 r / min; after drying and dehumidification, 3‰ stearyl stearate and 3‰ distearyl phthalate were added for surface coating modification at 90°C, the surface coating modification time was 20 min, the surface coating modification was carried out under stirring, and the stirring speed was 350 r / min; finally, the surface-coated calcium carbonate was cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0074] Comparative Example 5
[0075] 400 kg of calcite powder with a fineness of D50 of 2.1 μm, D97 of 5.5 μm and an oil absorption value of 31 mL / 100 g is dried and dehumidified at 110° C. The impregnation modification time is 30 min, and the drying and dehumidification is carried out under stirring at a stirring speed of 60 r / min. After drying and dehumidification, 20,000 parts of epoxy soybean oil, 20,000 parts of epoxy oleic acid butyl ester and 20,000 parts of epoxy oleic acid octyl ester are added to carry out impregnation modification at 65° C. for 30 min, and the impregnation modification is carried out under stirring at a stirring speed of 105 r / min. After the impregnation modification, the impregnated and modified calcium carbonate is cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0076] Comparative Example 6
[0077] 400 kg of calcite powder with a fineness of D50 of 2.1 μm, D97 of 5.5 μm and an oil absorption value of 31 mL / 100 g was dried and dehumidified at 110°C, the impregnation modification time was 30 min, the drying and dehumidification were carried out under stirring, and the stirring speed was 60 r / min; after drying and dehumidification, 3‰ distearyl phthalate and 3‰ pentaerythritol adipic acid-stearate were added to carry out surface coating modification at 90°C, the surface coating modification time was 20 min, the surface coating modification was carried out under stirring, and the stirring speed was 350 r / min; finally, the surface-coated calcium carbonate was cooled to room temperature and packaged to obtain heavy calcium carbonate with low oil absorption value.
[0078] The particle size distribution and oil absorption value of the heavy calcium carbonate with low oil absorption value prepared in Examples 1 to 9 and Comparative Examples 1 to 6 were tested.
[0079] The particle size distribution was tested using a BT-9300ST laser particle size analyzer produced by Liaoning Dandong Better Co., Ltd., where D50 represents the particle size value corresponding to 50% of the cumulative distribution; and D97 represents the particle size value corresponding to 97% of the cumulative distribution.
[0080] The test method of oil absorption value is: weigh 5g sample (accurate to 0.01), put it on a glass plate, stir the sample with a spatula, and slowly add dioctyl phthalate (DOP) and keep stirring until the added DOP completely bonds the sample together, that is, reaches saturation. Record the volume of DOP consumed.
[0081] Calculation of oil absorption: v / m*100,
[0082] Where, m: weight of the sample in g,
[0083] v: volume of DOP consumed, mL;
[0084] The unit of oil absorption is mL / 100g. The test results are shown in Table 1.
[0085] Table 1 Test results of heavy calcium carbonate with low oil absorption value of Examples 1 to 9 and Comparative Examples 1 to 6
[0086]
[0087]
[0088] As can be seen from Table 1, the oil absorption value of GY-616 (Comparative Example 1) is 28 mL / 100 g. After a single impregnation modification (Comparative Example 3), its oil absorption value is reduced to 23 mL / 100 g; after a single lubrication modification (Comparative Example 4), the oil absorption value is reduced to 22 mL / 100 g; after a two-stage modification, the oil absorption value is reduced to 15-17 mL / 100 g (Examples 1-4).
[0089] The oil absorption value of GY-716 (Comparative Example 2) is 31 mL / 100 g. After a single impregnation modification (Comparative Example 5), its oil absorption value is reduced to 26 mL / 100 g; after a single lubrication modification (Comparative Example 6), the oil absorption value is reduced to 24 mL / 100 g; after a two-stage modification, the oil absorption value is reduced to 16-18 mL / 100 g (Examples 5-9).
[0090] From the above results, it can be found that the method of the present invention can significantly reduce the oil absorption value of heavy calcium carbonate, and the heavy calcium carbonate with low oil absorption value prepared by the present invention has a good application effect in soft PVC.
[0091] Example 3, Example 9 and Comparative Examples 1-2 were formulated according to the formula in Table 2, wherein the stabilizer was a liquid barium zinc stabilizer. After being fully mixed, they were kneaded on a double-roll mill at 170° C. for 5 minutes, and film-drawn to obtain a 0.3 mm PVC film. The film-forming properties of the PVC film were tested, and the test results are shown in Table 2.
[0092] Table 2 PVC film formulation and film processing test results
[0093]
[0094]
[0095] As can be seen from Table 2, when 100g of PVC resin, 5g of stabilizer, and 45g of heavy calcium carbonate are used, different amounts of plasticizer DOP are required to maintain good film formation when different calcium carbonates are added. Comparative Example 1 and Comparative Example 2, which have not been subjected to surface modification treatment, cannot form a film when 30g of plasticizer is added, while the low oil absorption value calcium carbonate prepared by the present invention can form a good film when 30g of plasticizer is added, and the surface is bright. To achieve good film formation, 33g of plasticizer needs to be added to the untreated Comparative Example 1, and 35g needs to be added to Comparative Example 2. In other words, in the application of this formula system, the amount of plasticizer can be reduced by 3 to 5g when the low oil absorption value calcium carbonate of the present invention is used, which has a significant effect on reducing production costs for downstream application companies. At the same time, the small amount of plasticizer added can more effectively reduce the migration and precipitation of the plasticizer, which has a good help for the subsequent use performance of soft PVC.
[0096] The tensile strength and optical density of Formula 3, Formula 4, Formula 5 and Formula 7 with good film-forming properties were tested. The tensile strength test method was: using Chengde Jinjian Testing Instrument Co., Ltd. UTM-1422 universal mechanical properties testing machine according to GB / 1040-2018; the optical density test method was: using X-Rite Color Technology Co., Ltd. 341C densitometer. The test results are shown in Table 3.
[0097] Table 3 Tensile strength and optical density test results
[0098] Recipe ingredients Tensile strength(MPa) Optical density Recipe 3 13.89 0.65 Recipe 4 14.56 0.75 Recipe 5 13.21 0.55 Recipe 7 13.42 0.52
[0099] As can be seen from Table 3, the tensile strength of Formula 3 and Formula 4 obtained by using the low oil absorption heavy calcium carbonate prepared by the present invention is better than that of Formula 5 and Formula 7 obtained by Comparative Examples 1 and 2, indicating that the tensile strength of the film prepared by the surface-modified low oil absorption calcium carbonate is better than that of the unmodified calcium carbonate when the amount of plasticizer added is reduced. It can also be said that the heavy calcium carbonate modified by the present invention has good compatibility with PVC resin.
[0100] The optical density value is a representation of the light-shielding ability of the material, indicating the light density absorbed by the film. The larger the optical density value, the better the hiding power. The optical density values of Formula 3 and Formula 4 obtained by using the heavy calcium carbonate with low oil absorption value prepared by the present invention are greater than those of Formula 5 and Formula 7 obtained by Comparative Examples 1 and 2, indicating that the hiding performance of the film prepared by using the heavy calcium carbonate with low oil absorption value prepared by the present invention is better. The better the hiding performance, the longer the film can withstand outdoor use, and its service life will be longer.
[0101] As can be seen from the above embodiments, the present invention provides a heavy calcium carbonate with low oil absorption value and a preparation method and application thereof, wherein the heavy calcium carbonate with low oil absorption value is obtained by sequentially drying and dehumidifying, infiltration modification and surface coating modification of calcite powder. The two-stage modification process adopted in the present invention plays a role of wetting and dispersion in the first stage modification process, reduces the polarity of the surface of calcium carbonate, and makes the surface of heavy calcium carbonate have both polar groups and non-polar groups, which makes it easier to match with the ester modification auxiliary agent in the second stage modification process, and more easily forms a strong binding effect on the infiltrated calcium carbonate surface, fully realizing the improvement of the modification effect and reducing the oil absorption value.
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing heavy calcium carbonate with low oil absorption value, characterized in that: The following steps are involved: The calcite powder is sequentially subjected to drying and dehumidification, infiltration modification and surface coating modification to obtain heavy calcium carbonate with low oil absorption value; The modifying agent used in the impregnation modification is an epoxy plasticizer; The modifying agent used in the surface coating modification is an ester lubricant.
2. The method for preparing heavy calcium carbonate with low oil absorption value according to claim 1, characterized in that: The calcite powder meets the following conditions: D50 is 2-3 μm, D97 is 5.5-8 μm, and the oil absorption value is 25-35 mL / 100 g.
3. The method for preparing heavy calcium carbonate with low oil absorption value according to claim 1 or 2, characterized in that: The drying and dehumidification temperature is 105-120° C., the drying and dehumidification time is 10-50 min, and the drying and dehumidification is carried out under stirring, and the stirring speed is 30-90 r / min.
4. The method for preparing heavy calcium carbonate with low oil absorption value according to claim 3, characterized in that: The epoxy plasticizer includes one or more of epoxidized soybean oil, epoxidized linseed oil, epoxidized butyl oleate, epoxidized octyl oleate and epoxidized dioctyl tetrahydrophthalate.
5. The method for preparing heavy calcium carbonate with low oil absorption value according to claim 1, 2 or 4, characterized in that: The temperature of the impregnation modification is 50-80° C., the time of the impregnation modification is 15-60 min, and the impregnation modification is carried out under stirring, and the stirring speed is 50-150 r / min.
6. The method for preparing heavy calcium carbonate with low oil absorption value according to claim 5, characterized in that: The ester lubricant includes one or more of glyceryl monostearate, stearyl stearate, distearyl phthalate and pentaerythritol adipic acid-stearate.
7. The method for preparing heavy calcium carbonate according to claim 6, wherein The mass of the epoxy plasticizer is 0.4 to 0.9 of the mass of the calcite powder; The mass of the ester lubricant is 3-9‰ of the calcite powder.
8. The method for preparing heavy calcium carbonate with low oil absorption value according to claim 6 or 7, characterized in that: The surface coating modification temperature is 70-100° C., the surface coating modification time is 10-40 minutes, and the surface coating modification is carried out under stirring, and the stirring speed is 250-500 r / min.
9. A heavy calcium carbonate with low oil absorption value prepared by the preparation method according to claims 1 to 8, characterized in that: The low oil absorption heavy calcium carbonate meets the following conditions: D50 is 2 to 3 μm, D97 is 5 to 7 μm, and the oil absorption value is 15 to 18 mL / 100 g.
10. Use of the heavy calcium carbonate with low oil absorption value according to claim 9 as an auxiliary agent in soft PVC.